2022
DOI: 10.3389/fphar.2021.793346
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling in Pregnant Women Suggests Minor Decrease in Maternal Exposure to Olanzapine

Abstract: Pregnancy is accompanied by significant physiological changes that might affect the in vivo drug disposition. Olanzapine is prescribed to pregnant women with schizophrenia, while its pharmacokinetics during pregnancy remains unclear. This study aimed to develop a physiologically based pharmacokinetic (PBPK) model of olanzapine in the pregnant population. With the contributions of each clearance pathway determined beforehand, a full PBPK model was developed and validated in the non-pregnant population. This mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…There have been published PBPK models with observed good performance when compared with available data. 65,66 However, model predictions can be continually improved as more PK data in pregnant individuals are available to increase confidence. With continuous improvements to these models, they have the potential to be used to prioritize drugs that require more imminent study based on expected changes in PK.…”
Section: Data Interpretation and Translation Into Dosing Recommendati...mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been published PBPK models with observed good performance when compared with available data. 65,66 However, model predictions can be continually improved as more PK data in pregnant individuals are available to increase confidence. With continuous improvements to these models, they have the potential to be used to prioritize drugs that require more imminent study based on expected changes in PK.…”
Section: Data Interpretation and Translation Into Dosing Recommendati...mentioning
confidence: 99%
“…PBPK M&S approaches combine system‐dependent (anatomy, physiology, and other population characteristics) and drug‐dependent characteristics to mechanistically describe the PK of a drug and ultimately simulate untested clinical situations. There have been published PBPK models with observed good performance when compared with available data 65,66 . However, model predictions can be continually improved as more PK data in pregnant individuals are available to increase confidence.…”
Section: Considerations For Conducting Clinical Studies In Pregnant I...mentioning
confidence: 99%
“…Several PBPK modeling studies have predicted the pharmacokinetics of some antidepressants and antipsychotics during pregnancy, namely, sertraline, 101 paroxetine, 102 ziprasidone, 103 quetiapine, 104,105 aripiprazole, 105 and olanzapine. 106 George et al developed a PBPK model-informed web-based interactive tool that allows the gestational-agedependent prediction of sertraline pharmacokinetics at various doses, predicting an increase in sertraline plasma clearance of up to 143% in the late third trimester across various therapeutic doses (50-200 mg). 101 Biesdorf et al and Zheng et al found that ziprasidone and olanzapine exhibit relatively stable plasma exposures during pregnancy, 103,106 whereas quetiapine and aripiprazole doses should be increased, especially in late pregnancy, according to the modeling results presented by Badhan et al and Zheng et al 104,105 Many antipsychotics and antidepressants are extensively metabolized; therefore, alterations in fraction unbound and hepatic intrinsic clearance are likely to significantly affect the maternal drug exposure.…”
Section: Status and Opportunities For Modeling Studiesmentioning
confidence: 99%
“…Several PBPK modeling studies have predicted the pharmacokinetics of some antidepressants and antipsychotics during pregnancy, namely, sertraline, 101 paroxetine, 102 ziprasidone, 103 quetiapine, 104,105 aripiprazole, 105 and olanzapine 106 . George et al developed a PBPK model‐informed web‐based interactive tool that allows the gestational‐age‐dependent prediction of sertraline pharmacokinetics at various doses, predicting an increase in sertraline plasma clearance of up to 143% in the late third trimester across various therapeutic doses (50–200 mg) 101 .…”
Section: Status and Opportunities For Modeling Studiesmentioning
confidence: 99%
See 1 more Smart Citation